The Ottoman world : a cultural history reader, 1450-1700 - Karateke, Hakan T.; Anetshofer, Helga (University of California Press, 2021)
"The Ottoman lands, which comprised a geography extending from modern Hungary to the Arabian peninsula, were home to a vast population with a rich variety of cultures. The Ottoman World is the first primary source reader designed to reflect a wide and diverse set of voices across Ottoman society and bring them into the classroom. Written in many languages-not only Ottoman Turkish, but also Arabic, Armenian, Greek, Hebrew, Italian, and Persian-these texts span the extent of the early modern Ottoman empire, from the 1450s to 1700. Instructors are supplied with narratives conveying the lived experiences of individuals through texts that highlight human variety and accelerate a trend away from the 'state-centric' approach to Ottoman history. In addition, samples from court registers, legends, biographical accounts, hagiographies, short stories, witty anecdotes, jokes, and lampoons provide us with exciting glimpses into popular mindsets in Ottoman society. By reflecting new directions in the scholarship with its innovative choice of texts, this sourcebook will provide a vital resource for teachers and students"-- Provided by publisher.
Includes index.
Keywords: Turkey -- History -- Ottoman Empire, 1288-1918 -- Sources.; Turkey -- History -- Ottoman Empire, 1288-1918 -- Early works to 1800.; Empire ottoman -- Histoire -- Sources.; Empire ottoman -- Histoire -- Ouvrages avant 1800.; HISTORY / Middle East / Turkey & Ottoman Empire; Turkey; 1288-1918; Early works; History; Sources